NON-FUNGIBLE TOKEN (NFT) SEBAGAI ASET DIGITAL: SEBUAH FENOMENA DAN PERLINDUNGAN HUKUM KEKAYAAN INTELEKTUAL DI INDONESIA - Emmy Febriani Thalib; Ni Putu Suci Meinarni (Ganesha Civic Education Journal, 2022)
Non-Fungible Token (NFT) has recently become a social phenomenon as a new form of digital asset that is currently popular. In Indonesia itself, the development of NFT is fast in line with the development of the industry at the global level. Along with the more open and increasing understanding of block-chain, cryptocurrency trading or cryptocurrencies, as well as technological infrastructure that is increasingly supporting. The basic technical composition of the NFT is closely related to protecting the work from manipulation, duplication and reproduction. NFT technology is still very new and therefore, much of the scope of NFT is still unclear in terms of legal regulations in Indonesia. In terms of Intellectual Property, this study aims to determine the basic understanding of NFT and the Legal Protection of an NFT digital asset for creators, sellers and buyers. This article can also provide insight about NFT to the wider community so that they can read opportunities but can avoid the problem of copyright infringement and damage the concept of ownership in a work of art.